Synthesis of Di- and tri-tertiary amine containing methacrylic monomers and their (Co)polymerization via RAFT - Yu, B.; Lowe, Andrew (2009)
The synthesis, reversible addition-fragmentation chain transfer (RAFT) (co)polymerization, and aqueous phase behavior of three methacrylic monomers containing two or three pendent tertiary amine functional groups are described. Homopolymerizations were conducted with 1-methyi-1-cyanoethyl dithiobenzoate (CPDB) under bulk conditions following standard RAPT procedures. All three monomers, 1,3- bis(dimethylamino)propan-2-yl methaerylate (M1), l-(bis(3-(dimethylamino)propyl) amino)propan-2-yl methaerylate (M2), and 2-((2-(2-(dimethylamino)ethoxy)ethyl) methylamino)ethyl aerylate (M3), polymerized in a controlled manner as evidenced by the kinetic and molecular weight profiles. Homopolymerizations conducted at a lower ratio of CPDBrAIBN proceeded faster than those at a higher ratio. Subsequently, the facile eopolymerization behavior of M1 and M3 was demonstrated via the synthesis of a range of statistical copolymers with hexyl and lauryl methaerylate comonomers containing 10-90 mol % hydrophobic comonomer. Finally, the aqueoussolution characteristics of the M1-M3 homopolymers were briefly examined. All three homopolymers were shown to undergo phase transitions in aqueous media in response to changes in both temperature and pH. Specifically, 1 wt % solutions of polyMl were shown to possess an LCST of ~22 °C, that of polyM2 at ~33 °C, and for polyM3 the observed cloud point was ~63°C. Additionally, all homopolymers became hydrophobic and phase separated at high solution pH © 2009 Wiley Periodicals, Inc.